Effects of a short period of postural training on postural stability and vestibulospinal reflexes. - Claudia Grasso; Massimo Barresi; Maria Paola Tramonti Fantozzi; Francesco Lazzerini; Luca Bruschini; Stefano Berrettini; Paolo Andre; Cristina Dolciotti; Vincenzo De Cicco; Davide De Cicco; Paola d'Ascanio; Paolo Orsini; et al. (PLoS ONE, 2023)
The effects of postural training on postural stability and vestibulospinal reflexes (VSRs) were investigated in normal subjects. A period (23 minutes) of repeated episodes (n = 10, 50 seconds) of unipedal stance elicited a progressive reduction of the area covered by centre of pressure (CoP) displacement, of average CoP displacement along the X and Y axes and of CoP velocity observed in this challenging postural task. All these changes were correlated to each other with the only exception of those in X and Y CoP displacement. Moreover, they were larger in the subjects showing higher initial instability in unipedal stance, suggesting that they were triggered by the modulation of sensory afferents signalling body sway. No changes in bipedal stance occurred soon and 1 hour after this period of postural training, while a reduction of CoP displacement was apparent after 24 hours, possibly due to a beneficial effect of overnight sleep on postural learning. The same period of postural training also reduced the CoP displacement elicited by electrical vestibular stimulation (EVS) along the X axis up to 24 hours following the training end. No significant changes in postural parameters of bipedal stance and VSRs could be observed in control experiments where subjects were tested at identical time points without performing the postural training. Therefore, postural training led to a stricter control of CoP displacement, possibly acting through the cerebellum by enhancing feedforward mechanisms of postural stability and by depressing the VSR, the most important reflex mechanism involved in balance maintenance under challenging conditions.